EFEK 17β-ESTRADIOL TERHADAP DENSITAS RESEPTOR ADRENERGIK-αIDDAN KONTRAKTILITAS OTOT POLOS PEMBULUH DARAH TIKUS - Nurdiana, Nurdiana (Fakultas Kedokteran Universitas Brawijaya, 2008)
The incidence of hypertension in menopausal and post menopausal women related to plasma estrogen leveland sympathetic nervous activity. Estrogen may have a specific effect to modulate adrenergic vasoconstriction by modulating adrenergic receptors. Blood vessels contractility is regulated mainly by the sympathetic nervous system, in aorta mediated particularly by α1Dadrenergic receptor.We hypothesize that 17βestradiol decreases vascular smooth muscle contractility by decreasing α1Dadrenergic receptor density. To prove the above mechanism in the present study we performed several interrelated assays, i.e bioassay using isolated organ and protein blotting. An isolated rat aortic ring without endothelium (2-3 month,150-200 gram) was incubated in 17β-estradiol (10-5M, 10-4M,and 10-3M ) for two hours prior to stimulation using phenylephrine as α1Dadrenergic receptor agonist. The response of the rat aortic ring to the stimulation of α1Dadrenergic receptor agonist was measured as the subsequent change on aortic contractility using bioassay, and the change of α1Dadrenergic receptor density using Western and dotblot.